The Influence of the Learning Cycle Blended Learning Model on Student Learning Outcomes - Pratiwi Ajeng Safitri; Basori Basori; Febri Liantoni (Journal of Informatics and Vocational Education, 2023)
Learning in the 21st century requires students to be literate about the existence of technology. Technology users in Indonesia are increasing, but the quality of Indonesian education internationally, based on UNESCO records, is still far behind other ASEAN countries. COVID-19, once endemic in Indonesia, directly impacted education, which had to be carried out online. However, after Covid-19 subsided, learning was resumed face-to-face as usual. The Blended Learning learning model, suitable for the 21st century, should not be discontinued but should be improved and improved to make it more optimal. This research aims to determine the effect of the Learning Cycle Blended Learning model on student learning outcomes with the help of Moodle. This research uses quantitative methods with a quasi-experimental research design. This research involved 71 students in the experimental class with the Learning Cycle Blended Learning model and the control class with the Problem-Based Learning learning model. The instrument used is a learning outcomes test consisting of a pretest and a posttest. The t-test results show (1) differences in student learning outcomes between applying Problem-Based Learning and the 8E-Blended Learning cycle with a Sig value. (2-tailed) is 0.003. The n gain test results show (1) The 8E-Blended Learning cycle learning model is more effective in improving student learning outcomes with a gain score of 49.46 in the good category.